(untitled) (Revista de História da UEG (REVHIST), 2023)
This article aims to work on the concept of “scientific event” from the publication of Isaac Newton’s Philosophiae Naturalis Principia Mathematica in 1687. Our aim is to understand how, from this work, a space for debate, criticism and analysis was constituted of the Newtonian method, leading to the configuration of a kind of book-event in the Enlightenment period. By understanding that a historical event is a narrative construction mobilized by epistemological instruments that organize its plot, we will be able to investigate to what extent the Principia became a scientific event based on a network of readers that, in part, made Newton’s circulation possible in Europe XVIII century. The purpose of the debate is to understand how the constitution of the so-called Newtonianism was possible, not only after the publication of the book, marking a moment of rupture with the Aristotelian paradigm, but also the way in which the work was tied within a narrative that constituted it as a historical event. Keywords: Isaac Newton. Enlightenment; Scientific Event. Historical Event.